Psychiatric Disorders Are Associated with an Increased Risk of Injuries: Data from the Iranian Mental Health Survey (IranMHS) - Behrang SHADLOO; Abbas MOTEVALIAN; Vafa RAHIMI-MOVAGHAR; Masoumeh AMIN-ESMAEILI; Vandad SHARIFI; Ahmad HAJEBI; Reza RADGOODARZI; Mitra HEFAZI; Afarin RAHIMI-MOVAGHAR (Tehran University of Medical Sciences, 2016)
Background: Injuries and psychiatric disorders, notably both major public health concerns, are associated with a high burden and are believed to be bi-directionally correlated. Those inflicted with injuries face increased risks of mental illnesses. Psychiatric disorders may make the individual prone to injuries. The objective of the study was to assess the correlation of mental disorders with non-fatal injuries. Methods: A total of 7886 participants aged 15 to 64 yr were interviewed in a national household survey in 2011 in Iran. Composite International Diagnostic Interview (CIDI v2.1) was implemented to assess the prevalence of psychiatric disorders in the past twelve months. Injuries were assessed using Short Form Injury Questionnaire (SFIQ-7). Results: Injury was reported in 35.9% and 22.8% of participants in the past twelve and past three months, respectively. Using multivariate logistic regression analysis, mental disorders were significantly associated with injuries in the past three months (OR=1.6, 95% CI:1.36-1.87), recurrent injuries (OR=1.7, 95% CI: 1.21-2.41) and road/traffic accidents (OR=2.4, 95% CI: 1.28-4.49). Conclusion: Psychiatric disorders were found to be associated with an increased risk of injuries. Early detection and treatment of mental illnesses can contribute to injury prevention.